PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERASI PADA RSUD KABUPATEN ROKAN HULU (Studi Kasus Pegawai PNS Rumah Sakit Umum Daerah Rokan Hulu) - Murti Irwan; Machasin Machasin; Nuryanti Nuryanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine and analyze the effect of compensation and workenvironment on work motivation with job satisfaction as a moderating variable.The research method used in this study is to use primary data obtained bydistributing questionnaires to permanent employees who work at the Rokan HuluHospital, totaling 81 samples. The approach used is a quantitative approach. Thedata is processed using SPSS 21.0 software. The analysis used in this researchincludes validity test, reliability test, classical assumption test, and hypothesistesting. Based on the results of the analysis used, it can be seen that theIndependent variable, namely Compensation (X1) has no significant effect onWork Motivation (Y) and Work Environment (X2) has a significant effect on theDependent variable, namely Work Motivation (Y), and the Moderating variable,namely Job Satisfaction. (Z) succeeded in moderating the Work Environment onWork Motivation and for the Compensation variable it was not moderatedsuccessfully. This can be proven by looking at the regression equation that hasbeen obtained, namely: Work Motivation = 0.062 Compensation + 0.391 WorkEnvironment + 0.020 Interaction1 + -0.010 Interaction2. From the researchresults, it is also known that the coefficient of determination with Job Satisfactionas the moderating variable is obtained R2 = 0.339. These results indicate that33.9% of work motivation can be explained by independent variables andmoderating variables studied in this study and the remaining 66.1% is explainedby other variables not examined in this study..Keywords: Moderated Regression Analysis, Compensation, Work Environment,Job Satisfaction, Work Motivation.